Genotype–phenotype associations in PPGLs in 59 patients with variants in SDHX genes. Issue 8 (August 2020) - Main, Ailsa Maria; Rossing, Maria; Borgwardt, Line; Grønkær Toft, Birgitte; Rasmussen, Åse Krogh; Feldt-Rasmussen, Ulla
Abstract : Phaeochromocytomas and paragangliomas (PPGLs) are tumours of the adrenal medulla and extra-adrenal sympathetic nervous system which often secrete catecholamines. Variants of the SDHX ( SDHA, -AF2, -B, -C, -D ) genes are a frequent cause of familial PPGLs. In this study from a single tertiary centre, we aimed to characterise the genotype–phenotype associations in patients diagnosed with germline variants in SDHX genes. We also assessed whether systematic screening of family members resulted in earlier detection of tumours. The study cohort comprised all individuals ( n = 59) diagnosed with a rare variant in SDHX during a 13-year period. Patient- and pathology records were checked for clinical characteristics and histopathological findings. We found distinct differences in the clinical and histopathological characteristics between genetic variants in SDHB . We identified two SDHB variants with distinct phenotypical patterns. Family screening for SDHB variants resulted in earlier detection of tumours in two families. Patients with SDHA, SDHC and SDHD variants also had malignant phenotypes, underlining the necessity for a broad genetic screening of the proband. Our study corroborates previous findings of poor prognostic markers and found that the genetic variants and clinical phenotype are linked and, therefore, useful in the decision of clinical follow-up. Regular tumour screening of carriers of pathogenic variants may lead to an earlier diagnosis and expected better prognosis. The development of a combined algorithm with clinical, genetic, morphological, and biochemical factors may be the future for improved clinical risk stratification, forming a basis for larger multi-centre follow up studies.